(untitled) (Journal of Decolonising Disciplines, 2020)
Social unrest in South Africa has been characterised as nihilism. The injustice of racism and separatism in its historical and contemporary guises has diminished the sense of being fully human in the world. Racial and consumerist economic categories have become ways of determining the right and access to life. Such a dehumanising history, founded on hatred, can only be confronted through understanding the significance of justice. In this interview with renowned curator Khanyisile Mbongwa, we discuss the ways in which systemic violence and dispossession affect one’s sense of being. Mbongwa argues that it is only through self-love and mass political action against racial injustice that black self-realisation and liberation can be achieved. In some ways, Mbongwa’s work on South African townships as transitional spaces brings attention to the essence of South Africa’s politics: the animosity arising from severed social bonds and the corrosion of the love ethic. Love, as decolonial philosophy, is key to political solidarity.